THE POWER OF BU TEJO AND DIAN? THE ANALYSIS OF FEMINIST POWER RELATION IN THE FILM TILIK - Angjaya, Sonny (Capture : Jurnal Seni Media Rekam, 2021)
Tilik is a short film directed by Wahyu Agung Prasetyo. Given that the film's plot is primarily focused on the relationships of its female characters, the problem of female representation cannot be ignored. This article focuses on the power dynamic between the film's two central female characters, Bu Tejo and Dian, through the lens of Amy Allen's feminist perspective on power. The analysis identifies four dimensions of representation that contribute significantly to the development of their power relationship: physical appearance, marital status, gender role depiction, and socioeconomic status. The underlying significance of the power relationship between Bu Tejo and Dian in the film is analyzed through qualitative Content Analysis and Contextual Analysis approaches. This study reveals that the film portrays both women ambiguously, how patriarchal society creates an ecosystem that pits women against one another for power, and how the minor male characters in the film continue to exert signifficant influence over Bu Tejo and Dian in acquiring, maintaining, and exercising their power in a patriarchal society.